Minimally Invasive Medial Hip Approach for Treatment of Displaced Pipkin Type 1 Fractures: Surgical technique, quality of reduction and postoperative complications - Boonperm, Sanyakupta (Journal of Southeast Asian Orthopaedics, 2022)
Background: Treatment of femoral head fracture by surgical dislocation of the hip is claimed to provide full exposure of the femoral head but it is technically complex especially for inexperienced surgeon, and heterotopic ossification or trochanteric associated complications may be encountered. We adopted the minimally invasive medial hip approach technique originally proposed by Chiron to expose the displaced Pipkin type 1 fragment and report the surgical technique, quality of fragment reduction and immediate postoperative complication of this approach. Patients and Methods: Ten patients who had stable, congruence hip reduction and Pipkin type 1 fracture with residual fragment displacement more than 3 mm were operatively managed by medial approach. The procedure was performed as originally described by Chiron et al. The quality of fragment reduction was evaluated according to Matta's criteria. Patients were monitored for immediate postoperative complications. Results: Fragment fixation was performed in 9 patients and excision in another. Average operative time and blood loss was 96 minutes and 137 ml respectively. Postoperative fragment reduction quality was classified as anatomical in 4 and imperfect in 5 patients. There was no immediate postoperative complication. Conclusion: Minimally invasive medial hip approach is a safe and relatively simple alternative exposure for surgical treatment of displaced Pipkin type 1 fracture without immediate major complication. The fragment reduction performance is approaching those achieved by the surgical hip dislocation, with less extensile dissection, and neither osteotomy nor re-dislocation of the hip is necessary.